2022
DOI: 10.1002/adma.202207884
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Stretch‐Induced Microstructural Evolution and Morphology–Stretchability Relationships of High‐Performance Ternary Organic Photovoltaic Blends

Abstract: The stretchability and stretch‐induced structural evolution of organic solar cells (OSCs) are pivotal for their collapsible, portable, and wearable applications, and they are mainly affected by the complex morphology of active layers. Herein, a highly ductile conjugated polymer P(NDI2OD‐T2) is incorporated into the active layers of high‐efficiency OSCs based on nonfullerene small molecule acceptors to simultaneously investigate the morphological, mechanical, and photovoltaic properties and structural evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 74 publications
1
42
0
Order By: Relevance
“…Nevertheless, QD photodetectors generally present the inferior mechanical performance, which places great restrictions on their applications in wearable electronics. The great flexibility of organic semiconductors 103 may offer promising roads to enhance the mechanical performance of QPDs via the hybrid strategy. Moreover, our recent work has demonstrated that a promising elastomer can further enhance the mechanical performance of organic semiconductors, which is favorable for developing stretchable electronics.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, QD photodetectors generally present the inferior mechanical performance, which places great restrictions on their applications in wearable electronics. The great flexibility of organic semiconductors 103 may offer promising roads to enhance the mechanical performance of QPDs via the hybrid strategy. Moreover, our recent work has demonstrated that a promising elastomer can further enhance the mechanical performance of organic semiconductors, which is favorable for developing stretchable electronics.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the above research directions can enable the further performance and stability improvement of hybrid solar cells and thereby advance the progress toward commercialization. 223…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the prediction of mechanical properties of ternary blend lms is much more complicated, and prior efforts have met with only limited success. 22 Particularly, the theoretical understanding of new ternary blends based on dual donor polymers has not been This journal is © The Royal Society of Chemistry 2023 achieved thus far. Herein, we attempted to ll this gap by applying the knowledge of classic polymer mechanics.…”
Section: Prediction Of Mechanical Parametersmentioning
confidence: 99%
“…We noted that the equivalent box model (EBM) was used to predict the elastic modulus of multicomponent polymer systems. 22,[54][55][56][57][58] This motivated us to understand the ternary OSC systems with the EBM. As shown in Fig.…”
Section: Prediction Of Mechanical Parametersmentioning
confidence: 99%
See 1 more Smart Citation